Growth of Coﬀea arabica grafted onto Coﬀea canephora in presence of nematodes in nursery - Julca Otiniano, Alberto (2018)
In Peru, the performance of new grafted coffee cultivars (Coffea arabica L.) onto Coffea canephora, in the presence of Meloidogyne, has not yet been quantified, therefore, this essay had as objective to quantify the behaviour of six cultivars of coffee (Acaia, Catuai, Icatú Vermelho, Ibairi, Mundo Novo and Caturra Vermelho), grafted onto C. canephora, in the presence of these organisms. Plant height (A), shoot diameter (D), number of leaves (NH), fresh weight (PF), dry weight (PS) of plants, slenderness index (IE) and the Dickson quality index (ICD) were evaluated. The results showed the interaction between the type of cultivar and the nematodes, using C. canephora as a rootstocks. It is important to highlight the performance of Icatú Vermelho / Robusta (inoculated) and Caturra Vermelho / Robusta (inoculated), they showed a better performance facing the presence of nematodes.